The Effect of Budgetary Slack, Honesty Concern, and Desire to Honesty Managerial Budget Reporting - Maya Arisandy (Accounthink : Journal of Accounting and Finance, 2022)
This study examined the effect of budgetary slack, honesty concern, and desire to honesty managerial budget reporting. The object of this research is a manager in charge of purchasing management, finance, production, information systems and information quality, which is in the province of Banten, especially in Cilegon city. The city serve as a sample with 125 questionnaires distributed, but the questionnaire which can be processed as many as 51 questionnaires. Questions questionnaire measured with a scale of 1-5. Data were analyzed by using through SmartPLS (Partial Least Square) 1:10 version. The results of this study expressed that hypotesis from Budgetary Slack, Honesty Concern, and Desire is positive effect and significant to Honesty Managerial Reporting.